Effect of Brassica Oleracea Biscuit Supplementation on Immunity and Hemoglobin Levels in Pregnant Women: A Quasi-Experimental Study - Sari, Febriana; Simbolon, Rolasnih Lilista; Subroto, Edi; Trisnawati, Trisnawati; Sembiring, Jemalemna; Simanullang, Oca Floren; Ginting, Kartika Ovalia (Journal of Applied Nursing and Health, 2026)
Background: Maternal mortality remains a major concern, with anemia as a key contributing factor during pregnancy. Limited adherence to iron supplementation highlights the need for alternative approaches. Brassica oleracea, rich in essential nutrients, may support immune function and hemoglobin synthesis. This study aimed to evaluate the effect of this product in biscuit form on immunity and hemoglobin levels in pregnant women. Methods: A quasi-experimental study with a pre-test–post-test control group design was conducted. Baseline measurements were obtained from both intervention and control groups. The intervention group received Brassica oleracea biscuits in addition to standard care, while the control group received standard care alone. Post-intervention assessments were conducted in both groups. Results: There was a statistically significant difference in immune status between the intervention and control groups (p = 0.044). However, no significant difference in hemoglobin levels was observed between groups (p = 0.560). Conclusion: Brassica oleracea biscuit supplementation significantly improved immune status in pregnant women but did not result in a statistically significant difference in hemoglobin levels compared to standard care. These findings suggest that Brassica oleracea–based functional foods may serve as a complementary strategy to enhance maternal immunity during pregnancy.